Self-correcting Paths of Negativity and the Positive in Nature: A Revisiting of Schelling - Rivas, Virgilio Aquino (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
In the background of a renewed interest in Schelling’s late philosophy, the paper briefly explores several of his critical philosophical formulations integral to the beginnings and further development of the positive turn. This study begins with key insights in the Freedom essay, progressing into the Ages of the World and some later reflections on the conceptual and historical intricacies of mythology and revelation. I assign these works and formulations the function of serving as parallel vectors to the chronological unfolding of the positive or the ‘positive revealed’. For Schelling, the positive, which, in the final analysis, is nothing but God revealed by knowledge and ‘only in knowledge’, can only be posited from the negative, undergoing a rigorous self-correction process. In the paper, this process centres around the intricacies of explaining evil and the concepts of dual external worlds, parallel vectoring, reminiscent of Spinoza, the un-sublatable, etc., among other concepts that convey the naturalist underpinnings of Schelling’s positive philosophy. For comparative purposes, I will emphasise that this self-correction process shows the extent to which Hegel’s system can be considered a congruent path of negativity or flight of negativity coeval to the historical stages of realising the positive. The internal completion of Hegel’s system thus depends on the negative unfolding of knowledge in which the dialectic and its mediation process could only assume a minor role.